Central circuit mechanisms of itch - Chen, Xiao-Jun; Sun, Yan-Gang (Nature communications, 2020)
Itch, in particular chronic forms, has been widely recognized as an important clinical problem, but much less is known about the mechanisms of itch in comparison with other sensory modalities such as pain. Recently, considerable progress has been made in dissecting the circuit mechanisms of itch at both the spinal and supraspinal levels. Major components of the spinal neural circuit underlying both chemical and mechanical itch have now been identified, along with the circuits relaying ascending transmission and the descending modulation of itch. In this review, we summarize the progress in elucidating the neural circuit mechanism of itch at spinal and supraspinal levels. Itch is an important somatosensation, but the central mechanisms underlying it are not fully understood. Here, Chen and Sun review recent studies on the spinal and supraspinal circuits involved in itch processing.